Automatic Water Monitoring System For Tilapia Culture With Mobile Application (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This disquisition output will profit many people specially those who are adapting Tilapia Culturing.The pattern and sketch in this project evincive the implementation of an automatic water monitoring system for the tilapia culture. This system is automatically obtained and monitor important water parameters namely: Temperature and Potential Hydrogen (pH) level. I as a researcher, I discover also the problems when it comes into maintaining the water parameter needed by the fish without even frequently looking at the following: poor water maintenance system, contamination all over the water and number of tilapia dying by high or low ph level in water. The suitable attribute of the water monitoring system that must be improved to discourse the problems that I found out were: ph meter can make the process of water monitoring more enhance, faster, easier and the whole research output was be successfully improved water monitoring system that will help the research output to maintain the temperature of the water. When it comes to the ratings of the respondents for the Automatic Water Monitoring System for Tilapia Culture with Mobile Application were extremely receivable when it comes in the field of proficiency, performance, ability to give a good service and efficacy of this research output. To evade having a trouble or dilemma in monitoring water for tilapia culture, the government and the other authorities who have a power, they accommodate the correct usage of the propose system. One of the best way to avoid causing problem is to have a seminar that held by BFAR personnel, this seminar is all about how our technology helps to make proper reproduction of tilapia and with this action, they will get an idea to enhance and brought up a better system that the proponent produced.